2002
DOI: 10.1046/j.1440-1746.2002.02864.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor suppression and microcirculatory disturbance amelioration in ischemia/reperfusion injury of rat liver after ischemic preconditioning

Abstract: The suppression of tumor necrosis factor-alpha and the subsequent amelioration of microcirculatory disturbances were observed, suggesting that the mechanism underlying the protective effect of ischemic preconditioning in hepatic ischemia/reperfusion injuries may involve tumor necrosis factor-alpha and microcirculatory regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
6
0
4
Order By: Relevance
“…Indeed, PC attenuated morphological alterations and mucosal apoptosis partly by inhibiting the reactive oxygen species-mediated mitochondria-dependent pathway in the rat small intestine (19). Moreover, several studies showed that PC prevents intestinal ischemia-reperfusion injury by inhibiting leukocyte-endothelial cell interactions (2,33,47). The role of cell adhesion molecules like ICAM-1 and transmigration of neutrophils through the endothelial barrier is probably essential in gut barrier dysfunction (11).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PC attenuated morphological alterations and mucosal apoptosis partly by inhibiting the reactive oxygen species-mediated mitochondria-dependent pathway in the rat small intestine (19). Moreover, several studies showed that PC prevents intestinal ischemia-reperfusion injury by inhibiting leukocyte-endothelial cell interactions (2,33,47). The role of cell adhesion molecules like ICAM-1 and transmigration of neutrophils through the endothelial barrier is probably essential in gut barrier dysfunction (11).…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed specimens were embedded in paraffin, and 5-mthick sections were cut and then stained with hematoxylin and eosin (H&E). Tissue sections were also analyzed using terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL), intercellular adhesion molecule-1 (ICAM-1) immunohistochemical staining, and vascular cell adhesion molecule-1 (VCAM-1) immunohistochemical staining following our protocols for rat liver [23]. For the TUNEL assay, a commercial apoptosis detection kit (Intergen, Purchase, NY) was used.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…However, intravital microscopic studies in rodents are in agreement with our clinical data because they showed that IPC significantly reduced leukocyte-endothelial cell adhesion and microvascular perfusion disturbances and, hence, improved parameters of hepatocellular energy metabolism. 56,57 However, to identify more specifically the relative importance of the down-regulation of cytotoxic neutrophil functions among other mechanisms of liver protection induced by IPC, it would be imperative to deplete the number of circulating neutrophils or to use PMNL-adhesion-blocking antibodies, experimental tools that both are not applicable in humans and have not been used to this end even in animal studies to date. …”
Section: Relative Importance Of Attenuating Cytotoxic Neutrophil Funcmentioning
confidence: 99%